Socio-Demographic Determinants of Antepartum Fetal Death - Awoleke Jacob Olumuyiwa; Adanikin Abiodun Idowu (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2017)
Background: Antepartum fetal death (AFD) contributes significantly to stillbirths (SB) in low- and middle-income countries (LMIC). Modifying locally-prevalent demographic risk factors could lessen the burden of SB in the region.  Objective: This study seeks to identify the prevalence and modifiable socio-demographic risks for antepartum fetal death (AFD) in a Nigerian setting with the aim of recommending appropriate interventions to reduce the burden.  Method: Hospital-based 6 year (2009-2014) review of obstetric records at Ekiti State University Teaching Hospital (EKSUTH), Nigeria.  Results: Stillbirth (SB) rate was 29/1000 births and AFD rate was 22.5/1000 birth. AFD was more among women with age ≤20 years (93.8%), who had no antenatal care (83.2%), single (92.3%), with no formal education (95.6%), unskilled occupation (81.1%), parity ≥ 5 (92.3%), those with prior history of SB (81.0%) and Muslims (81.8%). Logistic regression analysis showed that absence of antenatal care (AOR: 3.32, 95% CI: 1.80-6.21, P<0.001) and lack of formal education (AOR: 0.18, 95% CI: 0.03-0.64, P= 0.005) significantly predict likelihood of AFD.  Conclusion: Absence of antenatal care and lack of formal education are associated with AFD during pregnancy. Educating women and health promotion towards improving the utilization of antenatal services can remarkably reduce the burden in low-resource settings.